Substrate-binding specificity of chitinase and chitosanase as revealed by active-site architecture analysis. (11th December 2015) - Liu, Shijia; Shao, Shangjin; Li, Linlin; Cheng, Zhi; Tian, Li; Gao, Peiji; Wang, Lushan
Highlights: The sequence profiles of the chitosanase and chitinase active sites are constructed. Substrate recognition is supported by hydrogen bonds with C2 functional groups. CH–π interactions contribute to tighter binding and processivity. Graphical Abstract: Abstract: Chitinases and chitosanases, referred to as chitinolytic enzymes, are two important categories of glycoside hydrolases (GH) that play a key role in degrading chitin and chitosan, two naturally abundant polysaccharides. Here, we investigate the active site architecture of the major chitosanase (GH8, GH46) and chitinase families (GH18, GH19). Both charged (Glu, His, Arg, Asp) and aromatic amino acids (Tyr, Trp, Phe) are observed with higher frequency within chitinolytic active sites as compared to elsewhere in the enzyme structure, indicating significant roles related to enzyme function. Hydrogen bonds between chitinolytic enzymes and the substrate C2 functional groups, i.e. amino groups and N-acetyl groups, drive substrate recognition, while non-specific CH–π interactions between aromatic residues and substrate mainly contribute to tighter binding and enhanced processivity evident in GH8 and GH18 enzymes. For different families of chitinolytic enzymes, the number, type, and position of substrate atoms bound in the active site vary, resulting in different substrate-binding specificities. The data presented here explain the synergistic action of multiple enzyme families at a molecular level and provide a more reasonable method for functional annotation, which can be further applied toward the practical engineering of chitinases and chitosanases.